Morphological and Molecular Identification of Acari: Ixodidae in Cattle, and Their Effect on Production. - Mustafa, Bahzad; Shakhawan Jalal Ahmed (University of Thi-Qar Journal of agricultural research, 2025)
This study examined the distribution and impact of Ixodid ticks on cattle in Sulaymaniyah Province, Iraq, utilizing both morphological and molecular identification methods. A total of 1,447 ticks were collected from 714 cattle across various districts, including Darbandikhan, Sharazur, Germian, and Qaradax, over three seasons: spring, summer, and autumn from August 2024 to May 2025. The highest infestation rate was observed in spring (58%), followed by summer (45%) and autumn (30%). No hard ticks were discovered on cattle during the winter months during this study. Morphological analysis identified two tick genera: Hyalomma (98%) and Rhipicephalus (2%). Molecular analysis of ITS2 rDNA regions confirmed the presence of one species of genus Hyalomma, Hyalomma anatolicum and two species of genus Rhipicephalus, Rhipicephalus bursa, and Rhipicephalus sanguineus.  Statistical analysis using t-tests and Z-tests for proportions highlighted significant seasonal discrepancies. Infestation rates varied significantly by season and geography, particularly among imported cattle, with Darbandikhan showing the highest prevalence. A questionnaire survey conducted with 100 cattle owners revealed high awareness of tick presence and associated health issues, including skin irritation and signs of tick-borne diseases. All respondents reported using chemical acaricides, though 30% suspected treatment resistance.